3P Invovlement in Software Requirement Engineering Process - Dave, Akshara B; Shah, S.M (International Journal of Computer Sciences and Engineering, 2025)
This paper focuses on software project management’s one of the important issues- 3P. 3P involves “People”, “Process” and “Product”. These are the key factors any project may have involved. Also it discusses various issues encountered while a project is being developed. Issues may be technical or personal. Main aim of this research paper is to focus on various aspects of software development and impact while key factors involved. The paper describes Software Requirement Engineering process in short and 3P involvement in them. People from various levels and of various levels participating to develop a product are often tend to succeed if followed a particular functioning. Concepts of 3P are discussed in terms of requirement engineering are explained in this research paper.